Menšiny ve městě: Projekt globální výchova - výchova k toleranci - Hadj Moussová, Zuzana (Lidé města, 2000)
The paper informs about a new program focusing on multi-cultural education which has started to be tested at a number of Czech schools. It is the program Global Education and Upbringing, destined for secondary school pupils. It is mainly devised to realize one's own cultural conditioning through experience activities. This helps understand cultural diversity of people from other cultures. The paper also summarizes the teachers' first experiences with the application of the program.